Search for the decay of a Higgs boson in the ℓℓγ channel in proton-proton collisions at s√=13s=13 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich (2018, 2018)
Title screen